Leggett, Decoherence, Style - Freitas, Fábio Henrique de Alencar (2021)
Decoherence is one of the most important subjects in contemporary research about foundations of quantum mechanics, but very little is known about how it became so and, even further, how it became a phenomenon. This work goes in the direction of answering the problem by focusing on the work of Anthony Leggett and how he was trying to challenge quantum mechanics. His research was mainly directed to finding concrete situations in which quantum mechanics would break down, but he ended up confirming even further the theory to new directions, including what would later be known as decoherence. All this confirmation heavily contributed to the development of physics, which awarded him the Nobel prize, but left him out of tune with other researchers on foundations of quantum mechanics. At the same time, while the majority of researchers on foundations faced problems in their careers, Leggett never faced any at all. To account for this, we use the idea of style of research and how this shaped the reception of Leggett’s work. As style is a concept that is originally from the field of art, we examined the controversy about it in aesthetics in order to reflect about it and find a suitable notion for our use. The result was the identification of style as an individual trait that is both intentional and controllable.